Tsinghua Science Park : a source of Chinese entrepreneurial innovation - McFarlan, F. Warren (Franklin Warren); Jia, Ning; Gao, Jian; Cao, Shanshan ([London] : SAGE, 2016)
With long willows and new cicada, blowing in the gentle breeze and rain in the early summer of 2014, Tsinghua Science Park, located just outside the East Gate of Tsinghua University, was filled with vibrant green colours. 20 years ago in the same place, were crumbling tenements, abandoned railways and small township enterprises, such as tyre and popsicle factories. Now, it is a centre for R&D headquarters of multinational companies, as well as headquarters of Chinese technology companies and other venture enterprises. As Tsinghua Science Park began to celebrate its 20th anniversary in August 2014, Mei Meng, Chairman of Tus-Holdings and founder of the Tsinghua Science Park, was actively preparing his team for the celebration.
Originally Published in: McFarlan, F. W., Jia, N., Gao, J. & Cao, S. (2015). Tsinghua Science Park - Source of Chinese Entrepreneurial Innovation. Beijing: Tsinghua SEM Chinese Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Tsinghua Science Park; Entrepreneurship -- China -- Case studies; Technological innovations -- China -- Case studies